PERANAN GURU DALAM MENGATASI KESULITAN BELAJAR SISWA DI SDN 1 PADANG REJO KECAMATAN PAGELARAN - Sari, Agis Amartia; Muhtarom; Abdul Hamid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the types of learning difficulties of students at SD N 1 Padang Rejo, in order to understand the steps taken by teachers in overcoming the learning difficulties of participants at SD N 1 Padang Rejo. This form of research uses a qualitative approach and descriptive research type. The results of this research show that students at SD N 1 Padang Rejo experience various difficulties in learning such as diffficulty writing, difficulty reading, difficulty communicating or focusing on the material being taught, difficulty conveying their ideas or opinions to other people, difficulty communicating well, difficulty solving difficult questions where Students must think critically and find it difficult to arrange words and sentences systematically and interestingly. Teachers take steps to eradicate the complexity of student learning, namely providing guidance and attention to students who experience difficulties in learning, using learning media, dan using interesting learning model. Teachers also relate the material taught to everyday life around students so that students can easily understand the concepts being taught.